2022
DOI: 10.47307/gmc.2022.130.s3.31
|View full text |Cite
|
Sign up to set email alerts
|

Development of an M-Learning application for early childhood education in emotional consciousness

Abstract: Mobile Learning (M-Learning) is an educational innovation strategy with the potential to contribute to the development of emotional awareness competencies in early childhood. For this reason, an application prototype was built with gamification elements aimed at preschool students, in four vulnerable educational contexts in the city of Popayan (Colombia). The design methodology followed an iterative process in four phases – Analysis, Design, Testing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…In my analysis of literature presented in this section, I observed that the adaptation concept traited by several methods. For exemple, in [5], the adaptation is attained by the constraction of models based an iterative process. The author in [6] propose a procedure of adaptation that used a set of predefined profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In my analysis of literature presented in this section, I observed that the adaptation concept traited by several methods. For exemple, in [5], the adaptation is attained by the constraction of models based an iterative process. The author in [6] propose a procedure of adaptation that used a set of predefined profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In this article [5], the authors developed an application prototype founded on "Gamification" foundations intended in preschool students, in four vulnerable educational contexts in Popayan city (Colombia). Design Methods studied an iterative process in four phases -Analysis, Design, Testing, Delivery -and resulted in end-user validation of the app's visual design, as well as software registration.…”
Section: Development Of An M-learning Application For Early Childhood...mentioning
confidence: 99%
“…(Nicolaidou et al, 2022) No Las aplicaciones de ludificación pueden constituir tecnologías eficaces de intervención conductual. (Torres-Rojas et al, 2022) No Los emoticonos y avatares son útiles para identificar emociones.…”
Section: Grupo De Control O Referenciaunclassified
“…El foco principal de los estudios ha sido el aprendizaje. En menor medida, otros autores se enfocaron en mejorar ciertas habilidades sociales de los niños (Nicolaidou et al, 2022;Riska et al, 2021;Torres-Rojas et al, 2022).…”
Section: Discusión Y Conclusionesunclassified